Yoga in pre-Columbian culture a yogic exposition (Munger Yoga Publications Trust, 2017)
Hidden information about Yoga in present time. Yoga is for humanity. It proves \x26 establishes that world wide this science was known to keep one fit and efficient in discharge of responsibilities.\nSpecifically it has brought out pre Colombian era \- yoga was practiced in Central and South America.\nA yoga lover who wish to know the historical facts about it , should read this book.
Keywords: Yoga; Yoga in art